'The Pain of Violence is a Powerful Silencer': African women writing about conflict - Farr, Vanessa (Canadian woman studies, 2000)
Yasmin Souka, Chair of South Africa's Human Rights Violations Committee (TRC), agreed. Enlarging on [Joyce Seroke]'s report, she described how, although more than 55 per cent of depositions to the TRC were received by women, it was rare that they were able to speak of their experiences as women, and even though efforts were made to arrange special hearings for women, the stigma of reporting sexual assault remained overpowering. Reinforcing the patriarchal lie that rape is something women secretly desire, women victims were regarded as "sell-outs" by the liberation movement in the 1980s. The legacy of this stigma prevails in the fact that there were very few accusations of sexual assault during the hearings, and even fewer admissions of sexual assault and applications for amnesty for this crime. Faced with the silence that surrounded the subject of war rape, the TRC was forced to rethink its handling of women's testimonies. Commissioners had to ask difficult questions: is sexual assault not perceived as a crime of the same magnitude as those which did attract amnesty appeals? Do perpetrators feel confident enough about their victim's silence to ignore this issue? Or is the real problem that mechanisms such as the Truth and Reconciliation Commission are not designed to be sufficiently sensitive to the particular forms of suffering endured by women? [Cynthia Cockburn]'s use of the word "homeland" has particularly ironic resonances for rural black South African women, who were specifically victimized by the centrality of the homeland system to the apartheid policy of "separate development." In 1951, only three years after the National Party came to power, the Bantu Authorities Act was promulgated to establish the basis for grand apartheid. Reserves, known as "homelands" were established as so-called "independent states" (recognized by no other nation except South Africa) to which black South Africans were forcibly removed. This carving up of the country was cornerstone of the regime's segregation policies, and permitted the National Party to exploit the most arable and/or mineral rich parts of the country and to create unprecedented prosperity for whites in South Africa. Dwellers in the homelands had no political rights, including citizenship, except for those afforded by their designated homeland, and could only enter the Republic to work if they held a valid pass. The possession of passes was largely restricted to men who were forced into migrant labour in mining and industry. Rural women were particularly dispossessed by apartheid policies, as they, along with children and the elderly, were considered "surplus population" whose movement away from the poverty of the rural areas was illegal. Women without passes could, and did, enter the vast squatter camps surrounding the cities of South Africa, but this placed them in a vulnerable position from which they could only participate in the informal economy -- as street vendors, beer makers, sex workers, or domestic labourers. The call to "Break the Silence!" has not, however, made for a less complicated public discourse about rape. Calculating that one woman is assaulted every 23 seconds in South Africa, and that one in two women in likely to be assaulted at least once in her lifetime,(f.5) Rape Crisis have not hesitated to shock the public into action. Statistics on sexual assault rates are, however, controversial and variable in South Africa, and can range anywhere from the claim above, to the more moderate argument that one in six women are assaulted. The National Institute for Crime Prevention and the Reintegration of Offenders (NICRO) Women's Support Centre in the Western Cape estimates that one in three women will be sexually assaulted at least once in her lifetime. This figure is derived from the official statistics of the South African Police Services, which tell a complex story of what is happening in the country with regard not only to the high rates of sexual assault, but also to public awareness and responsiveness to the problem. In 1993, reported sexual assaults in the Republic of South Africa numbered 27,037. In 1994, this figure increased by 18.75 per cent to 32,107. In 1995, there was an 8.33 per cent increase in reporting, and in 1996 this grew by an enormous 46.17 per cent, to total 50,841 assaults. In 1997, 52,160 attacks were reported, a 2.58 per cent increase over 1996 (http://www.womensnet.org.za).